2004
DOI: 10.1002/bin.176
|View full text |Cite
|
Sign up to set email alerts
|

Combining descriptive and functional analysis logic to evaluate idiosyncratic variables maintaining aggression

Abstract: For one boy with developmental disabilities, we conducted naturalistic observations and saw that aggression occurred during instructional task presentations. Next, in an experimental analysis, we manipulated the manner in which instructions were presented. Results showed that differentially high rates of aggression were observed when the manner in which instructions were presented was manipulated. Based on the results of the assessment, a successful intervention was developed that incorporated the idiosyncrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…However, we did not assess the degree to which the various FBA methods might be used in combination, so these data do not necessarily imply that informant and descriptive assessments are not being used in combination with functional analyses. For example, descriptive assessments might well be used to identify the kinds of variables to manipulate in a functional analysis (see Borrero, Vollmer, & Borrero, ). Still, because respondents indicated using informant and descriptive assessments more often than functional analyses, one could conclude that informant and descriptive methods are at least sometimes used alone to identify the function of behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not assess the degree to which the various FBA methods might be used in combination, so these data do not necessarily imply that informant and descriptive assessments are not being used in combination with functional analyses. For example, descriptive assessments might well be used to identify the kinds of variables to manipulate in a functional analysis (see Borrero, Vollmer, & Borrero, ). Still, because respondents indicated using informant and descriptive assessments more often than functional analyses, one could conclude that informant and descriptive methods are at least sometimes used alone to identify the function of behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Five articles (11.9% of sample) described variations in instructional style. Borrero, Vollmer, and Borrero () evaluated the extent to which abrasive instructions (i.e., exclamatory intonations, increased volume, and tense facial expression) versus pleasant instructions (i.e., smiling with a relaxed facial expression) evoked problem behavior for one individual after an initial functional analysis yielded unclear results. Elevated levels of problem behavior were observed with abrasive instructions.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have demonstrated that manipulating the style with which prompts are delivered (Borrero, Vollmer, & Borrero, 2004;Peyton, Lindauer, & Richman, 2005) and the way in which corrective feedback is provided (Ebanks & Fisher, 2003) can abolish the aversiveness of demands. For example, Peyton et al demonstrated that altering the how directive prompts were (e.g., from "show me the X" to "I wonder where the X is") successfully reduced escape maintained problem behavior in a 10 year old girl with autism.…”
Section: Manipulation Of Pre-session Variablesmentioning
confidence: 99%